ANALYSIS OF GRAMMATICAL COHESION ON STEVE HARVEY MOTIVATIONAL SPEECH - Rohit La Ami; Robby Satria (IKIP Siliwangi, 2024)
This research aimed to identify the grammatical cohesion devices in Steve Harvey’s speech, using a discourse analysis approach. The theory for this study was based on Halliday and Hasan's (1976) theory. Data collection was conducted through observation, involving watching, listening, and transcribing the speeches. The data was then analyzed using an identification method, where the context of each phenomenon was described, and the data was categorized according to the theory. The analysis revealed 10 references, 1 substitution, 1 ellipsis, and 3 conjunctions in the speech. The results indicate that the use of references dominates the speech delivered by the speaker, reflecting a strong reliance on this cohesive device to maintain clarity and continuity. Conjunctions are the second most frequently used grammatical elements, playing a crucial role in connecting various pieces of information and ideas throughout the speech. This frequent use of conjunctions helps to ensure that the speech flows smoothly and logically from one point to the next. Overall, these findings highlight the importance of cohesive devices in effective communication, particularly in public speaking. Understanding the role of these components can provide valuable insights into how successful speeches are constructed.